A Promising Candidate to Reliably Index Attentional Bias Toward Alcohol Cues–An Adapted Odd-One-Out Visual Search Task - Heitmann, Janika; Jonker, Nienke C.; de Jong, Peter J. (Frontiers in Psychology, 2021)
Attentional bias (AB) has been suggested to contribute to the persistence of substance use behaviour. However, the empirical evidence for its proposed role in addiction is inconsistent. This might be due to the inability of commonly used measures to differentiate between attentional engagement and attentional disengagement. Attesting to the importance of differentiating between both components of AB a recent study using the Odd-One-Out task (OOOT) showed that substance use was differentially related to engagement and disengagement bias. However, the AB measures derived from the OOOT showed insufficient reliability to be used as a solid measure of individual differences. Therefore, the current study aimed to improve the reliability of the AB measures derived from the OOOT by using more distinct contrast stimuli, adding practice trials, increasing the number of trials, and by having participants perform the task in an alcohol-relevant context. We contrasted the original OOOT with the adapted OOOT (i.e., OOOT-adapt), and assessed AB in low and high drinking individuals. Participants were 245 undergraduate students who typically tend to drink either low or high amounts of alcohol. In one condition, AB was measured with the original OOOT in a typical laboratory context, whereas in the other condition, AB was measured with the OOOT-adapt in a bar (i.e., alcohol-relevant) context. The OOOT-adapt showed superior internal consistency, especially for the high drinking group. Further, specifically the OOOT-adapt differentiated between low and high drinking participants showing that high drinkers faster engaged with alcohol cues than low drinkers. Thus, the OOOT-adapt was found to be a promising candidate to reliably index AB in the context of alcohol use. The OOOT-adapt further showed superior criterion validity as it could differentiate between low and high drinking individuals, thereby adding to the evidence that AB might be involved in substance use behaviour.